Experiences, learnings and perspectives in the regulation of agricultural biotechnology: the view from Argentina - Lewi, Dalia M.; Godoy, Perla; Simeone, Facundo (Frontiers in Bioengineering and Biotechnology, 2025)
Argentina has established itself as global leader in setting enabling regulations for agricultural biotechnology. Between 2020 and 2023 the responsible administration strengthened this position through the adoption of innovative regulations for New Breeding Techniques and fostering broad international collaboration. The experience accumulated during this period serves to illustrate best practices, current shortcomings, anticipate future challenges, and point to the solutions that the sector will need in the next few years.